Analysis of water consumption in Rzeszów during the refugee crisis from Ukraine - Rak, Janusz; Stręk, Magdalena; Ustrobiński, Marek; Potoczny, Robert (Instal, 2023)
The main aim of the work is to analyze the tap water consumption in Rzeszów during the refugee crisis from Ukraine after the start of the hostilities on February 24, 2022 by Russia. Various media data reported that the population of Rzeszów increased by as much as 100,000. This fact should be reflected in the consumption of tap water. The adopted unit water consumption of 0.15 m3/(Mk.d) shows that it increased from 13,000 to 15,000 new inhabitants. These data correlate with the number of assigned PESEL numbers, which in Rzeszów is 12,000.